Defending the State as a Form of Love for the Fatherland in an Islamic Perspective - Zamzami Zamie (International Journal of Nusantara Islam, 2016)
Transnational ideology springs the faded attitude of state defends. On another side, state defend is always connected with the military. The concept of jihad (struggle) in the Qur’an can be understood as an obligation to defend the state at all levels. The obligation could be in the form of guarding unity and integrity, culturalizing of deliberation, struggling justice, and maintaining freedom. The obligation of state defends in the form of physical form could not be conducted whether individually or collectively. This obligation is performed only if a ruler commands to battle against, and when an enemy has besieged a region. If defending Indonesia's state is one of the requirements for the existence and glory of Muslims in materializing Islamic values and universal of humanity, so struggling for state defend is a condition sine qua non.